Neurocognition and Social Cognition Predicting 1-Year Outcomes in First-Episode Psychosis - Lindgren, Maija; Holm, Minna; Kieseppä, Tuula; Suvisaari, Jaana (Frontiers in Psychiatry, 2020)
Cognitive performance at illness onset may predict outcomes in first-episode psychosis (FEP), and the change in cognition may associate with clinical changes. Cognitive testing was administered to fifty-four FEP participants two months after entering treatment and to thirty-nine participants after one year. We investigated whether baseline cognition predicted one-year outcomes beyond positive, negative, and affective symptoms and whether the trajectory of cognition associated with clinical change. Baseline overall neurocognitive performance predicted the one-year social and occupational level, occupational status, and maintaining of life goals. The domain of processing speed associated with the one-year remission, occupational status, and maintaining of life goals. Baseline social cognition associated with occupational status a year later and the need for hospital treatment during the first year after FEP. Most of the associations were retained beyond baseline positive and affective symptom levels, but when accounting for negative symptoms, cognition no longer predicted one-year outcomes, highlighting how negative symptoms overlap with cognition. The trajectory of neurocognitive performance over the year did not associate with changes in symptoms or functioning. Cognitive testing at the beginning of treatment provided information on the one-year outcome in FEP beyond positive and affective symptom levels. In particular, the domains of processing speed and social cognition could be targets for interventions that aim to improve the outcome after FEP.